The Comparison of Different Planes in Breast Ultrasonography - Altunkeser, Aysegul (Current Medical Imaging, 2015)
Aim: Breast ultrasonography (US) is a widely used and effective screening method, particularly in dense breasts. However, the fact that breast US examination takes a long time is one of the most important limiting factors. In this study, we investigated how to perform this important modality in the shortest time and in the most effective way, in terms of diagnostic usefulness. Materials and Methods: Breast ultrasonography was performed on 141 patients with the aim of screening and diagnosis. US was performed on both breasts in radial and transverse plus parasagittal planes, in which we compared the time spent during the examination and the efficiency of lesion detection. Additionally, we investigated whether the efficiency of lesion detection was related to age, weight, BI-RADS (Breast Imaging Reporting and Data System), breast parenchymal pattern, and lesion size. Wilcoxon, two-proportions and chi-square tests were used to compare variables. A p-value < 0.05 was accepted to be significant. Results: A total of 141 patients (mean age of 45) were included in the study. The mean time spent during the radial plane was ten minutes, while the transverse plus parasagittal plane took seven minutes (p<0.05). Moreover, parenchymal pattern and lesion size had a significant relationship with lesion detection (p<0.05). Lesion detection was more common in patients with type 3 pattern, especially in the radial plane. Conclusion: Screening US is important, especially in dense breasts. Despite the increased examination time, the radial plane must be the preferred method in order not to underestimate small size lesions.
Keywords: screening plan